The female gothic’s use of gossip - Mackechnie, Ann (My University, 2021)
Nineteenth-century novels uniquely combine recognisably Gothic terror, death and sometimes even romance. Yet in addition to the drama and suspense they create, they also focus on the plight of women. In this thesis I assert that nineteenth-century1 novels can foreground issues such as gender, class, and social angst so effectively because they leave room for female voices in the novel to be heard amidst the noise and privilege generated by their male counterparts.
A research report submitted in fulfilment of the requirements for the degree of Master of Arts by Research to the Faculty of Humanities, University of the Witwatersrand, 2021